ESRA19-0681 Gluteal pain and piriformis syndrome. (30th August 2019) - Krol, A
Abstract : Pain in the buttock? is it really a piriformis syndrome? Piriformis syndrome has been attributed to pain in infero-lateral quadrant of the posterior pelvis often associated with sciatica like symptoms, aggravated by walking, stooping and external hip rotation. However, other structures occupying greater sciatic foramen: gemellus superior and inferior, obturator internus, quadratus femoris and hamstring attachment to ischial tuberosity may be a source of pain and cause sciatic nerve entrapment at any level. Clinical examination with posterior pelvis ultrasound scan may help to find the exact location of pain and enhance diagnosis and treatment. Recent development of ultrasound in pain practice brings various specialities together in quest of diagnosis and solution.